Mapping the Nexus in the literature:The Influence of Entrepreneurial and Market Orientations on Supply Chain Agility - Lazarte-Aguirre, Andrea (2025)
Purpose – This study aims to map the relationship between entrepreneurial orientation (EO), market orientation (MO), and supply chain agility (SCA) from the operations perspective. An analysis of the most relevant manuscripts on the topic supposes a gap in the existing literature; thus, such an analysis was performed to evaluate consensus and discrepancies between scholars.  Design/methodology/approach – The literature review includes 13 papers published in Web of Science-indexed journals. These studies provide an overview of MO and EO on SCA. This review uses content analysis to map the nexus between these three capabilities. Findings – The results indicate that the literature can be clustered in four areas: (a) MO and EO with supply chain agility, (b) MO and supply chain agility, (c) EO and supply chain agility, and (d) supply chain orientation and other orientations as a research niche. The literature confirms the dominance of EO and MO in achieving SCA and demonstrates their combined effect as a dual strategic orientation in an organization. Originality/value – This study provides value to both researchers and policymakers in the areas of strategic management and supply chain by presenting the links between EO, MO, and SCA in a systematic and structured manner. In addition, it comprehensively identifies the gaps in previous research and provides avenues for future research.